2013
DOI: 10.1111/ffe.12101
|View full text |Cite
|
Sign up to set email alerts
|

Stress intensity factors calculation for surface crack in cylinders under longitudinal gradient pressure using general point load weight function

Abstract: General point load weight function (GPLWF) for a longitudinal semi‐elliptical crack in a thick‐walled cylinder with outer radius to inner radius ratio of 1.25 is derived. GPLWF is used to calculate stress intensity factors (SIFs) for any point along the crack front with the crack faces subjected to uniform and longitudinal gradient internal pressure. The comparison between the results obtained from the GPLWF and those available in the literature is presented, indicating an acceptable accuracy. The proposed GPL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…A careful analysis of our technique allows us to amend Eq. (14). Let α be the coordinate of the pole Q 0 .…”
Section: S T a R D O M A I N Smentioning
confidence: 99%
See 2 more Smart Citations
“…A careful analysis of our technique allows us to amend Eq. (14). Let α be the coordinate of the pole Q 0 .…”
Section: S T a R D O M A I N Smentioning
confidence: 99%
“…Some analytical weight functions available in the literature are able to relate the SIF at each point of an embedded planar two‐dimensional crack subjected to mode I loading or under mixed mode loading . The Oore‐Burns weight function displays a simple analytic form and gives an exact result in the special cases of penny‐shaped cracks or tunnel cracks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Ghajar and Saeidi Googarchin showed that this general form of WF can be used for surface cracks. 24,25 M…”
Section: W E I G H T F U N C T I O N M E T H O Dmentioning
confidence: 99%
“…Hence the instability extension of a hydraulic fracture can be analysed based on linear elastic fracture mechanics (LEFM) 17 . Stress intensity factor is not only an important parameter to express the crack-tip stress, but an important index to judge the crack instability state in LEFM 18 . Therefore, it is of great significance to analyse the distribution characteristics of the crack-tip stress field in an anisotropic material, understand the anisotropy of coal rock fracture toughness, and further study the complex extension rule of a hydraulic fracture.…”
mentioning
confidence: 99%